Effectiveness of Integrated Program Accelerate Reduction of Stunting and Poverty - Kusuma, Elvina Zerlinda; M, Mustainah; Kurnia, Intam (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
The purpose of this study is to analyze the Effectiveness of the Integrated Program for the Acceleration of Stunting and Poverty Reduction (Study in South Dolo District, Sigi Regency. This study uses a qualitative method with a descriptive approach. Data was collected through interviews, observations, and document analysis involving stakeholders such as local government officials, health workers, and community representatives. Based on the results of processing, discussion and analysis of research data, it can be concluded that the Effectiveness of the Program for the Acceleration of Stunting and Poverty Reduction in South Dolo District, Sigi Regency using the theory from Budiani (2007) is quite good when viewed from 2 aspects, namely Target Accuracy, Program Target Determination has been effective in seeing and collecting data on the criteria or categories of infants/toddlers affected by Stunting with their length and height below The normal range of standard height by age (TB/U) after measurement also shows a number below -2 standard deviation (SD). The second is Program Monitoring, the Monitoring Process is carried out periodically after being given additional food assistance by measuring the height and weight adjusted to the initial weight of the infant/toddler to determine the improvement in the development of Stunting infants/toddlers.In conclusion, this program has shown effectiveness in reducing stunting and poverty through systematic targeting and consistent monitoring mechanisms. However, further resource optimization and stakeholder coordination are still needed to maintain the long-term impact of the program